Co-designing food waste services in the catering sector. Issue 12 (11th October 2018) - Michalec, Aleksandra; Fodor, Martin; Hayes, Enda; Longhurst, James
Abstract : Purpose: The purpose of this paper is to present results from the action research project, where sustainability professionals, local businesses and academic researchers collaborated on exploring barriers for food waste recycling in SMEs food outlets in order to inform local policy and business practices in Bristol, UK. Design/methodology/approach: The researchers conducted face-to-face, qualitative surveys of 79 catering businesses in three diverse areas of the city. The action research methodology was applied, where a range of co-researchers contributed towards study design and review. Findings: The research reveals the main barriers to recycling and how such perceptions differ depending on whether the respondents do or do not recycle, with "convenience" and "cost" being the main issue according to the already recycling participants. On the other hand, participants who do not recycle state that their main reason is "not enough waste" and "lack of space". Practical implications: Participants recommended a range of measures, which could improve the current food waste services in Bristol. For example, they suggest that business engagement should address the barriers voiced by the participants applying the framings used by them, rather than assuming restaurants and cafes are not aware of the issue. By inviting a variety of non-academic stakeholders into the process of research design and analysis, the project addressed the imbalances in knowledge production and policy design. Originality/value: Despite the local and qualitative focus of this paper, the results and research methodology could act as a useful guide for conducting food waste action research in the policy context.